Bottom currents and sediment waves on a shallow carbonate shelf, Northern Carnarvon Basin, Australia. (15th April 2017) - Belde, Johannes; Reuning, Lars; Back, Stefan
Abstract: The modern seafloor of the Australian Northwest Shelf between Exmouth and Dampier was analyzed for large scale sedimentary bedforms on 3D seismic reflection data. The Carnarvon MegaSurvey of Petroleum Geo-Services (PGS), a merged dataset of multiple industrial 3D seismic reflection surveys with a total size of 49, 717 km 2, offers an extensive view of the continental shelf, slope and rise of the Northern Carnarvon Basin. Over the shelf two fields of large scale sediment waves were observed in water depths between 55–130 m, where the seafloor may be influenced by different processes including internal waves, tides and storms. Based on the dimensions and orientations of the sediment waves the dominant direction and approximate strength of local bottom currents could be estimated. Information on local sediment grain-size distribution was provided by the auSEABED database allowing a classification of the observed sediment waves into sand- or mudwaves. The first sediment wave field is positioned northwest of the Montebello Islands where the shelf is comparatively narrow and local sediment is mainly sand-sized. It most likely formed by increased bottom currents induced by the diversion of tidal flows around the islands. The second sediment wave field is located north of the Serrurier and Bessieres Islands within a local seafloor depression. Local sediments are poorly sorted, containing significant amounts of mud and gravel in addition to the mainly sand-sized grains. The coarser sediment fraction could have been reworked to sandwaves by cyclone-induced bottom currents. Alternatively, the finer sediment fraction could form mudwaves shaped by less energetic along-slope oriented currents in the topographic depression. The sediment waves consist partially of carbonate grains such as ooids and peloids that formed in shallow water during initial stages of the post glacial sea-level rise. These stranded carbonate grains thus formed in a different environment than the sediment waves in which they were redeposited. In fossil examples of similar high-energy ramp systems this possible out-of-equilibrium relationship between grains and bedforms has to be taken into account for the interpretation of the depositional environment. Highlights: The Northern Carnarvon Basin seafloor was analyzed using 3D seismic reflection data. Two large scale sediment-wave fields were observed in water depths between 55–130 m. Bottom currents induced by tidal flows and cyclones formed sandwaves. Less energetic slope parallel currents could have formed mudwaves. Sandwaves incorporate relict and stranded shallow-water carbonate grains.